THE IMPACT OF ADMINISTRATIVE COMMUNICATION ON ACHIEVING THE EFFECTIVENESS OF ADMINISTRATIVE DECISIONS IN BAGHDAD, IRAQ COMPANIES - Dr Aklas Khedir Dara (Scholars Digest Publishing, 2023)
This study investigates the impact of administrative communication on the effectiveness of administrative decisions in companies based in Baghdad, Iraq. A mixed-methods research design was adopted, with a sample of 200 employees from diverse managerial levels. The research analyzed different facets of administrative communication, such as the effect of communication channels, cultural and linguistic barriers, hierarchical structures, and technology use, among others. The results indicate a strong correlation between efficient administrative communication and effective decision-making. The study suggests improvements in communication practices and technology use, highlighting the need for an open communication environment and transparent decision-making processes.
Keywords: Administrative Communication, Decision-Making, Organizational Communication, Administrative Decisions, Collaborative Decision-Making, Communication Barriers, Hierarchical Structures, Technology Use in Communication, Baghdad Companies.